Electoral Manipulation Informationally on Hoax Production in 2019 Presidential and Vice Presidential Election in Indonesia - Wildhan Khalyubi; Aditya Perdana (Mengeja Indonesia Publisher, 2021)
This research aims to explain the hoax phenomenon with the concept of electoral manipulation in the form of information on the holding of 2019 Presidential and Vice Presidential General Election. Hoax problems in elections are often found in several countries such as Venezuela, France, the United States, and Indonesia. This research is qualitative research by combining primary and secondary data. Primary data was obtained through interview techniques with several institutions concerned about elections and hoaxes. Meanwhile, secondary data was obtained through literature, news, and documentation which support this research. As Alberto Simpser’s view in this research expresses, electoral manipulation aims to increase the influence of groups of political actors on citizens as voters. Electoral manipulation was seen as a tool to win the upcoming elections and as a tool to influence people's behavior - elites, citizens, bureaucrats, organizations, politicians, and others - with excessive and blatant manipulation seeming logical. Therefore, this research found that by linking hoaxes as a form of informational electoral manipulation, it is found that hoaxes do not only attack political opponents. However, hoaxes as a part of electoral manipulation in the form of information have implications for efforts to delegitimize public trust in electoral organizers, especially the General Election Commission (KPU).